PENINGKATAN SIKAP DAN DISIPLIN SISWA SMK MENGGUNAKAN ALAT PELINDUNG DIRI DALAM PEMBELAJARAN K3 - Mariani; Subijanto; Agus Amin Sulistyono (Jurnal Penelitian Kebijakan Pendidikan, 2020)
The improvement of attitude and disciplinary behavior of vocational school students in using personal protective equipment is part of standard operating procedures according to applicable regulations. Desk research is used as a method of the study. The purpose of the study is to examine and provide policy suggestions to improve student disciplinary attitudes and behavior when working in a culinary workshop/laboratory/kitchen.. The results of the study show that 1) the attitude and behavior of student work discipline in practicing using personal protective equipment are still not fully following the rules of law work safety and healthy; 2) the practice room is not equipped with a set of personal protective equipment including pictures/posters of occupational safety and health. This study concludes that the use of personal protective equipment as part of efforts to establish a work ethic and graduate competence is important for the implementation of workplace safety and health in line with the demands of the world of work in the era of globalization. It is concluded that the implementation of occupational safety and health using personal protective equipment has not been enforced in compliance with legislative requirements and needs to be incorporated as part of the profile of vocational high school graduates.